2008
DOI: 10.1021/ja801341m
|View full text |Cite|
|
Sign up to set email alerts
|

Pyridine Ligand Rotation in Self-Assembled Trigonal Prisms. Evidence for Intracage Solvent Vapor Bubbles

Abstract: The rate of interconversion of the two inequivalent edges of the pyridine rings in the trigonal prism 3c, self-assembled from 3 equiv of the star connector, tetrakis[4-(4-pyridylethynyl)phenyl]cyclobutadienecyclopentadienylcobalt, and 6 equiv of a platinum linker, cis-(Me3P)2Pt(2+) 2 TfO(-), was determined by DNMR in nitromethane. It exhibits a highly unusual bilinear Eyring plot. In the low temperature regime, the activation enthalpy DeltaH(double dagger) is approximately 12 kcal/mol and an activation entropy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
40
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 35 publications
5
40
1
Order By: Relevance
“…35 We propose that they pertain to the first steps of cage unraveling and thus the last steps in the mechanism of its self-assembly, and to the structure of the solvent around and/or inside the cage.…”
Section: Discussionmentioning
confidence: 99%
“…35 We propose that they pertain to the first steps of cage unraveling and thus the last steps in the mechanism of its self-assembly, and to the structure of the solvent around and/or inside the cage.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical studies showed that largest trifacial box, 404 , displayed a highly unusual kinetic behavior during the pyridine ligand rotation. 464 …”
Section: Three Dimensional (3d) Nanoscopic Cagesmentioning
confidence: 99%
“…[2] Thec oordination geometry of the metal ions and the number of the binding sites of the ligands and overall structure of the ligand define geometry of the coordination assembly.The use of divalent or tetravalent Pd II of cis-, trans-, or square-planar binding geometry,t ogether with various rigid or flexible pyridyl ligands,has proven to be asuccessful strategy in obtaining numerous supramolecular assemblies.In general, the ligands used for their preparation are mostly symmetrical, relatively rigid, and very often achiral. [6,7] TheM 3 L 6 assembly is represented by work of Fujita et al, where 608 8 donor,1 ,2-bis(ethynylpyridine)benzene, in combination with Pd II ,y ielded solvato-controlled assemblies of Pd 3 L 6 and Pd 4 L 8 . [4] Focusing on the chiral concave coordination assemblies resembling the structures presented and starting from the smallest ones,several examples of chiral metallo-supramolecular rhomboids have been prepared by self-assembly of chiral bis-pyridyl-substituted ditopic ligands with 908 8 cis-blocked Pd II ,o ften with [(enPd)(NO 3 ) 2 ].…”
mentioning
confidence: 99%